PEMBENTUKAN LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI MCDONALD’S - Cahyadi, Enggar; Santosa, Eric (Jurnal Ilmiah Telaah Manajemen, 2005)
Loyalty of a firm’s customer has been recognised as the dominant factor in a business organization’s success. This research serves to add to the knowledge in service marketing literature and helps us extend our understanding of the relationship between customer loyalty and customer satisfaction. The proposed model of service quality is based on a current conceptualizations of service quality, which suggests that service qualiy is a multidimensional and hierarchical construct (Brady & Cronin, 2001). In this model service quality consists of three primary dimensions which are defined by several coresponding subdimensions (a) interaction quality - employee attitude, employee behavior, and employee expertise, (b) physical environment quality -ambient condition, design, and equipment, (c) oucome quality - waiting time, physical change, valence. Using data collected from McDonald's Restaurant, the finding indicated that customer satisfaction with the restaurant performance is an important factor in influencing customer loyalty. Among the restaurant performance, the service quality and price provided by restaurant are the most important factor in determining customer satisfaction.